PENGELOLAHAN RISIKO RANTAI PASOK PRODUK OLAHAN BANDENG PADA UD. ARSHAINDO MENGGUNAKAN METODE HOUSE OF RISK - Al Basthomi, M Yazid (JUSTI (Jurnal Sistem dan Teknik Industri), 2024)
ABSTRACT Milkfish is one of the types that dominates the total production of this pond culture because it is one of the most potential fish species to be cultivated because of the fish's viability, which is 10,208.23 tons based on data from the East Java Province Fisheries and Marine Service in the last 207 updated in 2019 The increase in the aquaculture yield has triggered the owners of UKM (Small and Medium Enterprises) which are developing in Gresik Regency to process the milkfish. Opportunities for processing milkfish into other products make this product a higher selling value compared to fresh milkfish which is sold directly to consumers. The large number of parties involved in the process or supply chain causes risk to arise, therefore it is necessary to identify the risk of SMEs and design a handling strategy for the risks that exist in the related SMEs. The House Of Risk method is used in identifying risks and providing risk management strategies for the dominant risk causes. This method consists of 2 stages, namely the risk identification stage and the causes of risk or called the House Of Risk Phase 1 and the risk management phase or the House Of Risk Phase 2.The House Of Risk 1 phase shows that in the related SMEs there are 24 types of risk and 20 types of risk causes. which exists. In calculating the ARP and using the Pareto diagram, the results show that there are 5 causes of dominant risk in these UKM. The House Of Risk 2 phase results in 5 risk management strategies for 20 causes of dominant risk. Keywords :House Of Risk, Milkfish, Risk Identification, Risk Management